PENGARUH PEMBERIAN IBA DAN KOMPOSISI MEDIA TERHADAP PERTUMBUHAN STEK Sansevieria cylindrica var. patula - Sesar Fikri Firmansyah; Rochmatino Rochmatino; Kamsinah Kamsinah (Scripta Biologica, 2014)
Sansevieria is an ornamental plant commonly known as mother-in-law's tongue, devil's tongue, and snake tongue. It has many functions e.g. uses as medicine, its fiber for the textile industry, and as indoor air pollutants absorber. However, the growth of Sansevieria is slow. Therefore the supply of it seeds in large quantities in the short time was difficult. The use of Plant Growth Regulator (PGR) was one solution to accelerate the propagation of Sansevieria leaf cuttings. This study aimed to determine the concentration of IBA and the composition of media to increase the leaf cuttings propagation of Sansevieria cylindrica var. patula. The method was randomized block design with factorials. Factor I was the IBA concentrations comprised of  K0 at 0 ppm, K1 at 50 ppm, K2 at 100 ppm, K3 at 150 ppm, and K4 at 200 ppm. Factor II was the ratio of manure:sand:rice-husk-ash as the growth media, comprised of M1 with 1:1:1 ratio, M2 with 1:2:1 ratio, and M3 with 1:1:2 ratio respectively. Each with three replicates overall was 45 experimental units. The parameters observed were a percentage of propagated cuttings, the number of roots, the longest length of roots, the number of shoots. The results showed the IBA could not increase the growth of cuttings in all media composition; however media compositions could enhance the number of shoots. The effective media composition propagated the cuttings was the M1 a 1:1:1 ratio of manure:sand:rice-husk-ash.